INVESTIGATING ENVIRONMENTAL CONCERNS FOR PRIMARY SCHOOL TEACHERS - Siti Patonah; Sentot Budi Rahardjo; Cari Cari; Sajidan Sajidan (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The success of environmental education in schools is largely determined by the teacher's factors at school. The purpose of this research is to get the teacher's view of the environmental concern. This research method is a cross sectional survey. The survey was conducted randomly to 950 elementary school teachers who were scattered in two locations of the PLPG program in Central Java in 2017. Obtained 148 samples from 10 regencies and cities in 1 rayon and 1 sub rayon. The results obtained indicate that the knowledge of elementary school teachers' environment is in good condition even though it has not directly influenced attitudes, or habits.